Examining export performance in CARICOM from 1992-2006 : an application of the revealed comparative advantage measure - Lorde, Troy ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2008)
Computes and analyzes changes in export performance based on revealed comparative advantage for CARICOM countries over 1992-2006 using data at the 1-digit SITC level.